Escherichia coli O157:H7 Requires Intimin for Enteropathogenicity in Calves - Dean-Nystrom, Evelyn A. (American Society for Microbiology, 1998)
Enterohemorrhagic Escherichia coli (EHEC) strains require intimin to induce attaching and effacing (A/E) lesions in newborn piglets. Infection of newborn calves with intimin-positive or intimin-negative EHEC O157:H7 demonstrated that intimin is needed for colonization, A/E lesions, and disease in cattle. These results suggest that experiments to determine if intimin-based vaccines reduce O157:H7 levels in cattle are warranted.